Blood purification with CytoSorb in critically ill COVID‐19 patients: A case series of 26 patients. Issue 11 (6th July 2021) - Nassiri, Amir Ahmad; Hakemi, Monir Sadat; Miri, Mir Mohammad; Shahrami, Reza; Koomleh, Azadeh Ahmadi; Sabaghian, Tahereh
Abstract: Severe forms of the coronavirus disease 2019 (COVID‐19) can progress to sepsis‐like complications accompanied by "cytokine storm" for which the most effective treatment has not yet been established. Our study describes the results of CytoSorb hemoadsorption in COVID‐19 patients treated on the intensive care unit (ICU). In this retrospective study, 26 patients with COVID‐19 and acute respiratory distress syndrome (ARDS) were treated with hemoadsorption therapy. Pre‐, and post‐treatment values (clinical and laboratory) were compared. Data are expressed as mean (confidence intervals, CI), or median [interquartile ranges, IQR], as appropriate. Patients received 2 hemoadsorption treatments. This resulted in a significant decrease in norepinephrine requirements, and inflammatory marker plasma concentrations (procalcitonin, C‐reactive protein, ferritin) when comparing pre versus post treatment levels. The PaO2 /FiO2 and overall organ function (ie, Sequential Organ Failure Assessment—SOFA score) also improved significantly. Patients stayed on the ICU for 9 days and 21 of them survived. To the best of our knowledge, this is one of the largest case series to date reporting early experiences on extracorporeal hemoadsorption therapy in SARS‐CoV‐2 positive patients with hyperinflammation and moderate ARDS. Treatment proved to be effective, technically feasible and well‐tolerated. Abstract : Graphical abstract depicting inclusion criteria, treatment modalities and main outcomes.